Case Report: A Missense Mutation of KIT in Hyperpigmentation and Lentigines Unassociated With Systemic Disorders: Report of a Chinese Pedigree and a Literature Review - Yang, Lu; Liu, Yuehua; Wang, Tao (Frontiers in Medicine, 2022)
Background: KIT is a proto-oncogene which is involved in proliferation, survival, and regulation of melanocytes, mast cells and the interstitial cells of Cajal. Mutations of KIT have been reported to be associated with hyperpigmentation and lentigines, mastocytosis, and gastrointestinal stromal tumors (GISTs). Some hotspot mutations of KIT have been reported to be associated with mastocytosis and GISTs. While the relationship between KIT mutations and hyperpigmentation and lentigines has not been fully elucidated. Methods: In this study, we presented a three-generation Chinese pedigree with progressive hyperpigmentation and generalized lentigines inherited in an autosomal dominant pattern. High-throughput sequencing was performed to capture genetic variations in peripheral blood samples of the proband. And Sanger sequencing was performed to further verify the result. We also reviewed previous literature of KIT mutations with hyperpigmentation and lentigines. Results: A missense mutation of KIT gene was identified: c. 2485G>C, which was co-segregated in the proband and his insulted father. Germline KIT mutations presenting as generalized hyperpigmentation and lentigines without systemic disorders are rare, with only two reports of c. 2485G>C mutation associated with this phenotype in previous literature. Conclusion: Our pedigree, together with those two reports, indicates a possible phenotype-genotype correlation of this germline KIT mutation, which might be helpful for genetic counseling, further functional segregation of KIT and design of targeted therapy in the future.